AKTIVITAS ANTIBAKTERI EKSTRAK KULIT PISANG KEPOK KUNING (Musa paradisiaca L.) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli SERTA PENENTUAN TOTAL FLAVONOID DAN FENOL DALAM FRAKSI AKTIF - Wahyuni, N. K. D. M.S.; Rita, W. S.; Asih, I. A. R. A. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019, 2019)
Peel of yellow kepok banana ( Musa paradisiaca L). has not been used optimally, while the peel can be used as an infection medicine The aim of this study was to reveal the activity of kepok yellow banana peel extract against Staphylococcus aureus and Escherichia coli and to determine the total content of flavonoids and phenols in active extract.. Extraction peel of yellow kepok banana was done by maceration and partition method, anti bacterial activity was assayed by wells diffusion method, determination total flavonoid and phenolic contents was done by UV-Vis Spectrophotometer. Maceration of 1 kg peel of yellow banana produced 80.9173 g of crude ethanol extract. The partition of 20 g crude ethanol extract produced 1,3758 g of n-hexane extract, 3,5818 g of ethyl acetate extract, and 1,0762 g of n-butanol extract. Anti bacterial test result showed that the 10% n-butanol extract was active towards S.aureus and E.coli with strong activity compared with ethanol, ethyl acetate, and n-hexane extract. MIC value was 0.5% for S.aureus and 0,2% for E.coli bacteria. The contain total flavonoid and phenol in n-butanol extract respectively were 0.06% and 0.15%.